2016
DOI: 10.1007/978-3-319-21756-7_14
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Artificial Sodium and Potassium Ion Channels

Abstract: In Nature, all biological systems present a high level of compartmentalization in order to carry out a wide variety of functions in a very specific way. Hence, they need ways to be connected with the environment for communication, homeostasis equilibrium, nutrition, waste elimination, etc. The biological membranes carry out these functions; they consist of physical insulating barriers constituted mainly by phospholipids. These amphipathic molecules spontaneously aggregate in water to form bilayers in which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 310 publications
0
5
0
Order By: Relevance
“…5 These membrane nanotubes mimic the structure and properties of natural ion channels. 6 Although the SCPNs compete with them in the transport efficiency of alkali ions, the ion selectivity is far from the natural systems. In addition, studies carried out with transmembrane SCPNs have shown that some transport selectivity can be achieved playing with nanotube internal diameter, 5 e.g., decapeptides efficiently transported glucose or glutamic acid while octapeptides did not.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 These membrane nanotubes mimic the structure and properties of natural ion channels. 6 Although the SCPNs compete with them in the transport efficiency of alkali ions, the ion selectivity is far from the natural systems. In addition, studies carried out with transmembrane SCPNs have shown that some transport selectivity can be achieved playing with nanotube internal diameter, 5 e.g., decapeptides efficiently transported glucose or glutamic acid while octapeptides did not.…”
Section: Introductionmentioning
confidence: 99%
“…7 The remarkable combination of efficiency and transport selectivity of natural ions channel continues spurring the scientific interest in the design of improved artificial systems. 6 Some of the protein channels, such as potassium channels, 8 have a shape characterized by the presence of a selectivity filter in the centre of the channel that is preceded by a dilated water-filled chamber. Therefore the form of the internal cavity of these proteins resembles the shape of Venturi tubes.…”
Section: Introductionmentioning
confidence: 99%
“…One-dimensional hollow spaces are found in well-aligned and uniform nanochannels, 35 nanotubes, 36 synthetically designed channels, 37,38 and crystalline building blocks with ordered channels. 39,40 These spaces act as linear channels, confining the configuration and pathway of ions along the axial direction when ions enter the channel.…”
Section: Confined Nanostructures In Membranes For Ion Transportmentioning
confidence: 99%
“…Selective transport of cations across the cell membrane is important for many fundamental biological processes such as maintaining the resting potential of cells, skeletal muscle contraction, nerve impulse transmission and hormonal secretion. [ 1–5 ] Natural ion transporters have complex structures and are typically made of large proteins. [ 1,2 ] Despite the high ion‐selectivity and precise functions of natural ion transporters, their poor in vitro stability has inspired researchers to develop stable and structurally simple biomimetic ion transporters.…”
Section: Figurementioning
confidence: 99%